2017
DOI: 10.1038/s41598-017-02741-w
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and Outcomes of Suspected Infections of the Central Nervous System in Children in Mbarara, Uganda

Abstract: Infections of the central nervous system (CNS) are severe conditions, leading to neurological sequelae or death. Knowledge of the causative agents is essential to develop guidelines for case management in resource-limited settings. Between August 2009 and October 2012, we conducted a prospective descriptive study of the aetiology of suspected CNS infections in children two months to 12 years old, with fever and at least one sign of CNS involvement in Mbarara Hospital, Uganda. Children were clinically evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Children who met the criteria above were enrolled into a prospective descriptive cohort study between August 2009 and October 2012. A more complete description of the study population and methods is provided elsewhere [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Children who met the criteria above were enrolled into a prospective descriptive cohort study between August 2009 and October 2012. A more complete description of the study population and methods is provided elsewhere [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Socio-demographic and clinical characteristics of the participants including age, gender, HIV exposure, history and type of previous treatment as well as clinical information at admission and discharge and treatment received were recorded in a standardized case report form [ 11 ]. Diagnosis at admission was based on clinical examination and systematic testing with a rapid diagnostic test for malaria (SD-Bioline Malaria Antigen P.f/Pan, Standard Diagnostics, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48] In a recent study in Uganda, a diagnosis of tuberculous meningitis was confirmed in 4% of children suspected of meningitis. 49 Data are missing in West African countries where HIV prevalence is lower.…”
Section: Ta B L E 1 Description Of Primers and Probesmentioning
confidence: 99%